2019
DOI: 10.1002/dneu.22703
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Tyrosine Hydroxylase Gene Expression in Embryonal Carcinoma Stem Cells Using a Natural Tissue‐Specific Inducer

Abstract: A large number of studies have focused on the generation of dopaminergic neurons from pluripotent cells. Differentiation of stem cells into distinct cell types is influenced by tissue-specific microenvironment. Since, central nervous system undergoes further development during postnatal life, in the present study neonatal rat brain tissue extract (NRBE) was applied to direct the differentiation of embryonal carcinoma stem cell line, P19 into dopaminergic (DA) phenotypes. Additionally, a neuroprotective drug, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…In the previous study, we showed that neonatal whole brain extract could induce DA phenotype with high expression of TH gene in P19 cells. In addition, LC-MS/MS analysis confirmed the presence of factors related to neuronal differentiation in NRBE content (Momendoust et al, 2019 ). The existence of cytokines, growth factors, and some other peptides in the developing and adult rat brain tissue has been proved previously (Pettmann et al, 1986 ; Bartlett et al, 1991 ; Lindholm et al, 1992 ; Lee et al, 1993 ; Mogi et al, 1994 ).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…In the previous study, we showed that neonatal whole brain extract could induce DA phenotype with high expression of TH gene in P19 cells. In addition, LC-MS/MS analysis confirmed the presence of factors related to neuronal differentiation in NRBE content (Momendoust et al, 2019 ). The existence of cytokines, growth factors, and some other peptides in the developing and adult rat brain tissue has been proved previously (Pettmann et al, 1986 ; Bartlett et al, 1991 ; Lindholm et al, 1992 ; Lee et al, 1993 ; Mogi et al, 1994 ).…”
Section: Discussionmentioning
confidence: 87%
“…Sox-2 can control pluripotency and neural differentiation of human pluripotent stem cells (Khoo et al, 2013;Zhang and Cui, 2014). Downregulation of Sox-2 in the differentiated cells derived from stem cells has been wellestablished previously (Ebrahimie et al, 2014;Mehrfarjam et al, 2016;Momendoust et al, 2019). IHowever, it is reported that depending on the environmental input, Sox-2 could function as a pluripotency and, or neural differentiation factor (Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the effect of neonatal rat brain extract (NRBE) on neural differentiation of an EC stem cell line, P19, was approved. 30 , 31 Furthermore, the effects of neonate mouse pancreas extract (MPE)/conditioned medium (PCM) on the differentiation of P19 cells into pancreatic β-cells have been demonstrated previously. 29 , 32 MPE was also able to induce trans -differentiation of bone marrow mesenchymal stem cells into IPCs.…”
Section: Discussionmentioning
confidence: 95%